Extent of Test Anxiety among Nursing Students in Oman and impact on academic performance - , Mohammed Ghalib Qutishat, MSN, RN; , Arcalyd Rose Cayaban, MSN, RN; , Michael Leocadio, DNM, RN (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Background: Tests and examinations are considered to be one of the major sources of anxiety among students world-wide. Purpose: to examine the extent of test anxiety among nursing students and its impact on their academic performance. Method: a descriptive correlational design was used. A sample of 153 nursing students participated. The Test Anxiety Scale (TAS), social-demographic, and academic background were used. Results: 153 nursing students participated, the majority of them were female; 118 (77.1%), are studying a regular nursing program; 134 (87.6%), are not under study probation; 21 (86.3%) are in their 3rd and 4th academic year 95 (62.1%). The majority of the students have moderate test anxiety or worry 66 (43%), impairment 85 (56%) and overall 85 (55.6%). Discussion: the results of the study revealed that it is important to collaborate all efforts starting from nursing colleges, faculties, and administrators to develop consulting services on anxiety management strategies to optimise students’ performance. Implication: Guidance programs on study skills consultation, and workshops on a national basis should be to implement in the curriculum.